Deskripsi Kecerdasan Visual Spasial Siswa dalam Memecahkan Masalah Bangun Ruang Sisi Datar Ditinjau Berdasarkan Tingkat Kemampuan Awal Geometri pada Siswa Kelas VII SMP - Anisah Syafiqah; Ruslan; Darwis (Issues in Mathematics Education (IMED), 2020)
The aim of this research is to determine the general description of spatial visual intelligence of students from grade VII of SMP in solving solid figure flat side problems based on the initial ability level of geometry. This research used Hass Theory which classifies the characteristics of spatial visual intelligence based of imagining, conceptualizing, problem solving, and problem seeking. The type of this research is descriptive research with qualitative approach. The research subjects were 3 students. The first subject has high initial ability in geometry, the second subject has moderate initial ability, and the third subject has low initial ability. The research instrument used consists of the initial ability of geometry test questions, spatial visual intelligence of solid figure flat side test questions, and interview guidelines. The research result showed that: (1) The most dominant characteristic that appears in students was the characteristic of problem seeking and imagining, while the least dominant characteristic was problem solving. (2) Subjects who had high initial ability of geometry was able to fulfill 3 spatial visual intelligence characteristics, those were imagining, conceptualizing, and problem seeking. (3) Subjects who had moderate initial ability of geometry was able to fulfill 2 spatial visual intelligence characteristics, those were imagining and problem seeking. (4) Subjects who had low initial ability of geometry was not able to fulfill all the characteristics of spatial visual intelligence.